ДАЈУ ЛИ ЉУДСКА ПРАВА МОГУЋНОСТ ЗА ОСНАЖИВАЊЕ ДРУШТВЕНО ОСЈЕТЉИВИХ ГРУПА У СОЦИЈАЛНОМ РАДУ У РЕПУБЛИЦИ СРПСКОЈ? - Šućur-Janjetović, Vesna; Rakanović Radonjić, Andrea; Gajić, Draško (Srpska politička misao, 2023)
Vulnerable groups represent special categories that are in a higher risk of being socially excluded, vulnerable and sensitive to spectrum of risks, including poverty. Disabled persons, children, youngsters, women, elders, victims/survivors of violence, illiterate people, people living in rural areas, members of certain minority groups, refugees and displaced persons, members of LGBTIQ+ communities etc, are considered to be vulnerable. Human rights as a universal concept are guaranteed by the Constitution of Bosnia and Herzegovina (BiH), which guarantees the implementation of human rights for all citizens of BiH. The obligation to implement the international documents that secure the standards, obliging the state to enforce guaranteed human rights is also anticipated by the Constitution. Human rights are the foundation and the framework for social work and social policy when it comes to working with and in favour of vulnerable groups, however, in reality of social work practice, these groups remain on the margins of society. This article focuses on possibilities of social work in helping vulnerable groups to move from the margins of society. The article represents the results of the analysis conducted on gathered relevant documents that include information regarding the current state and processes, status and changes regarding the vulnerable groups’ human rights enforcement in Republic of Srpska. The theoretical framework used for understanding and trying to search for possible answers to the defined question is underpinned by the critical social work perspectives. The content analysis was used as an independent theoretical-empirical method when research on relevant documents was conducted.